HERMENEUTICS SITUATION AS THE PHILOSOPHIZING METHOD OF MARTIN HEIDEGGER AND ITS RELEVANCE TO SOCIAL RESEARCH - Anam, Rifqi Khairul (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
Applying natural science methodologies to the social sciences causes a crisis in science. A crisis of science means the narrowing of researcher subjectivity so the possibility of research heuristics is drastically reduced. Martin Heidegger a philosopher of existentialism tried to solve this problem by developing a method that integrated schools of phenomenology and hermeneutics. This research aims to describe the hermeneutics situation method which embodies the two things above. This research is a type of library research that is descriptive and qualitative. The important value and novelty of this research is that it examines the closeness of philosophy and social science through Martin Heidegger’s way of thinking. A researcher does not live in isolation, he is connected to the context of life in which he lives. The context of life motivates researchers to see the meaning of something. In social research, researchers do not just meet social facts, but meet appropriate events (ereignis). So, social researchers are advised to avoid two things when conducting social research in the context of hermeneutics situation, namely the principle of subject-object division and the value-free principle. The reason is a presumption that a researcher was involved in the surrounding environment which then becomes the object of his research, even before conducting the research. This involvement is what makes the researcher able to understand the object of his research.